Tetramethylpyrazine ameliorates indomethacin-induced gastric ulcer in rats: Impact on oxidative, inflammatory, and angiogenic machineries - Huda M. AlKreathy; Mohammed K. Alghamdi; Ahmed Esmat (Elsevier, 2020)
Available antiulcer medications reveal partial efficacy and numerous adverse reactions. Tetramethylpyrazine (TMP) was known for its potential antioxidant, anti-inflammatory and angiogenic properties. The aim of current study was to investigate the potential gastroprotective effect of TMP against indomethacin-induced gastric ulcer in rats with possible underlying mechanisms. TMP was tested at 3 doses (15, 30 & 60 mg/kg/d po) three days before indomethacin challenge (25 mg/kg ip). Gastric tissue was evaluated morphologically and histopathologically. Oxidative statuses were assessed via glutathione content (GSH), malondialdhyde (MDA) and catalase (CAT) activity, while TNFα and IL-6 were measured as inflammatory mediators. Gastric PGE2 was investigated in addition to vascular endothelial growth factor (VEGF). TMP was effective (at 30 and 60 mg/kg/d) in promoting mucus secretion and preventing histopathologic changes induced by indomethacin. Mechanistically, TMP significantly enhanced GSH content and CAT activity while reducing lipid peroxidation as expressed by MDA concentration. Moreover, TMP effectively reduced TNFα, IL-6 and intracellular adhesion molecule (ICAM-1) concentrations. On the other hand, TMP enhanced both COX-1 and PGE2 and encouraged angiogenesis via increasing VEGF expression. In conclusion, TMP possesses a protective effect against indomethacin-induced gastric ulcer. This could be explained - at least partly - by its antioxidant, anti-inflammatory and angiogenic effects.